Traumatic Brain Injury-Induced Sex-Dependent Changes in Late-Onset Sensory Hypersensitivity and Glutamate Neurotransmission - Krishna, Gokul; Bromberg, Caitlin; Connell, Emily Charlotte; Mian, Erum; Hu, Chengcheng; Lifshitz, Jonathan; Adelson, P. David; Thomas, Theresa Currier (Frontiers in Neurology, 2020)
Women approximate one-third of the annual 2.8 million people in the United States who sustain traumatic brain injury (TBI). Several clinical reports support or refute that menstrual cycle-dependent fluctuations in sex hormones are associated with severity of persisting post-TBI symptoms. Previously, we reported late-onset sensory hypersensitivity to whisker stimulation that corresponded with changes in glutamate neurotransmission at 1-month following diffuse TBI in male rats. Here, we incorporated intact age-matched naturally cycling females into the experimental design while monitoring daily estrous cycle. We hypothesized that sex would not influence late-onset sensory hypersensitivity and associated in vivo amperometric extracellular recordings of glutamate neurotransmission within the behaviorally relevant thalamocortical circuit. At 28 days following midline fluid percussion injury (FPI) or sham surgery, young adult Sprague-Dawley rats were tested for hypersensitivity to whisker stimulation using the whisker nuisance task (WNT). As predicted, both male and female rats showed significantly increased sensory hypersensitivity to whisker stimulation after FPI, with females having an overall decrease in whisker nuisance scores (sex effect), but no injury and sex interaction. In males, FPI increased potassium chloride (KCl)-evoked glutamate overflow in primary somatosensory barrel cortex (S1BF) and ventral posteromedial nucleus of the thalamus (VPM), while in females the FPI effect was discernible only within the VPM. Similar to our previous report, we found the glutamate clearance parameters were not influenced by FPI, while a sex-specific effect was evident with female rats showing a lower uptake rate constant both in S1BF and VPM and longer clearance time (in S1BF) in comparison to male rats. Fluctuations in estrous cycle were evident among brain-injured females with longer diestrus (low circulating hormone) phase of the cycle over 28 days post-TBI. Together, these findings add to growing evidence indicating both similarities and differences between sexes in a chronic response to TBI. A better understanding of the influence of gonadal hormones on behavior, neurotransmission, secondary injury and repair processes after TBI is needed both clinically and translationally, with potential impact on acute treatment, rehabilitation, and symptom management.